51 Changing needs and geographical variation in palliative care for lung cancer. (30th January 2023) - Robinson, Mark; Robinson, Justin; Pring, Andy; Verne, Julia
Abstract : Introduction: 26, 935 people died from lung lancer (2020) in England. 1 year survival remains low, so palliative care remains a critical part of care for lung cancer patients. Aims: To use national linked Office for National Statistics mortality and hospital episode statistics (ONS-HES) to describe variation in geographical need and opportunities for improving palliative care (PC) for lung cancer patients. Methods: A sub-set of an ONS-HES linked mortality dataset for England with people who died with lung cancer as the underlying cause (ICD-10 C33–34) was analysed for: age at death, gender, need for early PC (1-year survival), and proxy indicators of quality: place of death, >3 emergency admissions in last 90 days (3+EAs), seen by Palliative Care Team (PCT) in final admission. Results: Provisional results. 51% of people dying from lung cancer in 2020 were aged >75 years and 47% female. Both age at death and% females have increased significantly over the past 2 decades. One year survival (2019) varied across CCGS from 40.2–57.7%. The% of lung cancer patients dying at home in England jumped from 33.3% (2019) to 44.0% (2020), home becoming the commonest place for the first time. However, this varied 31.6–57.2% across CCGs. 3+EAs dropped from 12.6% (2019) to 10.5% (2020) but significant variation persistent across NHS Regions 9.5–12.0%. The% seen by (PCT) in final hospital episode increased from 33.2% (2012) to 45.5% (2019), varying 21.3–62.1% across CCGS. Conclusions: Analysis of national and local data demonstrates the need for and quality of PC for lung cancer patients. Impact: Commissioners and providers should note: increasing females and >75 years patients, variation in final admission PCT input and need for early PC (1-year survival).